A pre-lithiated silicon oxide negative electrode material and preparation method thereof

By covering the surface of the silicon oxide with hydrophobic conductive carbon layer, hydrophilic carbon layer and hydrophobic inorganic substances, and prelithiation by gas phase coating and hydrothermal method, the problems of material structure failure and electrochemical performance degradation caused by high temperature in the existing methods are solved, and efficient prelithiation and excellent electrochemical performance are achieved.

CN117080403BActive Publication Date: 2025-02-28HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311186384.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-14
Publication Date
2025-02-28
Estimated Expiration
2043-09-14

AI Technical Summary

Technical Problem

The existing prelithiation of silicon oxide in silicon oxide requires high temperature calcination, resulting in material structural damage and electrochemical performance degradation.

Method used

通过在氧化亚硅表面均匀覆盖疏水导电碳层、亲水碳层,并在两层间分散疏水无机物,采用气相包覆工艺和水热法进行预锂化,降低温度并保持材料结构的均一性。

Benefits of technology

Prelithiation of prelithiation at lower temperatures is achieved, reducing disproportionation of sub-silicon oxide and surface structure failure, and improving the electrochemical performance and stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117080403B_ABST
    Figure CN117080403B_ABST
Patent Text Reader

Abstract

The present invention provides a pre-lithiated silicon oxide negative electrode material and a preparation method thereof, and relates to the technical field of silicon negative electrode material preparation. The core of the pre-lithiated silicon oxide negative electrode material includes an amorphous silicon oxide containing a lithium silicate phase, and the outer surface of the core is uniformly covered with a hydrophobic conductive carbon layer and a hydrophilic carbon layer in sequence, and a hydrophobic inorganic substance is uniformly dispersed between the hydrophobic conductive carbon layer and the hydrophilic carbon layer. The pre-lithiated silicon oxide negative electrode material and metallic lithium form a half-cell for electrochemical performance testing, the test rate is 0.1C (first time) + 0.5C (cycle), the charge and discharge voltage is 0.005-1.5V, the discharge specific capacity of the negative electrode plate can reach 1630-1730mAh / g, the first efficiency is 89.0%-92.0%, and after 50 cycles, the capacity can still be maintained at 89.9%-90.9%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of silicon negative electrode material preparation, and in particular to a pre-lithiated silicon monoxide negative electrode material and a preparation method thereof. Background Art

[0002] At present, with the promotion and popularization of electric vehicles, the energy density requirements for batteries are also increasing. Traditional graphite negative electrode materials can no longer meet the current needs. Silicon has a high theoretical specific capacity (4200mAh / g), but it has a huge volume effect (≥300%) during the charge and discharge process. Silicon oxide has a smaller volume effect (~200%) and a higher specific capacity, and has great commercial potential as a negative electrode material for lithium batteries.

[0003] However, during the first lithium insertion process, a SEI film will form on the surface of silicon oxide, and a large amount of lithium silicates (Li4SiO4, Li2SiO3, Li2Si2O5) will be formed inside. These reactions cannot be reversed, resulting in a large amount of irreversible consumption of lithium sources, resulting in low initial efficiency of silicon oxide and affecting battery energy density. Therefore, silicon oxide pre-lithiation technology has been widely studied and promoted, that is, silicon oxide materials are charged with lithium before full electrical cycling, and irreversible lithium silicates are formed before electrochemical cycling, completing volume pre-expansion, improving the initial coulombic efficiency, and reducing volume changes during charging and discharging.

[0004] Currently, the most common method for pre-lithiation of silicon oxide is solid-phase calcination. However, this method requires high-temperature calcination. During the pre-lithiation process, silicon oxide will be disproportionated to produce silicon grains, which will destroy the internal structure of silicon oxide. In addition, due to uneven solid-solid reactions or local solid-liquid reactions on the surface, local reactions will be violent and uneven, destroying the surface structure and affecting the electrochemical properties of the material. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In view of the deficiencies in the prior art, the present invention provides a pre-lithiated silicon monoxide negative electrode material and a preparation method thereof.

[0007] (II) Technical solution

[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0009] A pre-lithiated silicon oxide negative electrode material, wherein the core of the pre-lithiated silicon oxide negative electrode material comprises amorphous silicon oxide containing a lithium silicate phase, the outer surface of the core is uniformly covered with a hydrophobic conductive carbon layer and a hydrophilic carbon layer in sequence, and a hydrophobic inorganic substance is uniformly dispersed between the hydrophobic conductive carbon layer and the hydrophilic carbon layer.

[0010] Preferably, the amorphous silicon oxide particle size of the lithium silicate phase is 5 to 8 μm, the thickness of the hydrophobic conductive carbon layer is 25 to 40 nm, and the thickness of the hydrophilic carbon layer is 10 to 30 nm.

[0011] Preferably, the hydrophobic inorganic substance includes one or more of copper oxide, aluminum oxide, silver oxide, aluminum phosphate, and aluminum metaphosphate.

[0012] On the other hand, a method for preparing a pre-lithiated silicon oxide negative electrode material comprises the following steps:

[0013] S1: Silicon oxide particles are coated with a hydrophobic conductive carbon layer on the surface of silicon oxide to obtain powder A;

[0014] S2: Pour the powder A into an inorganic aqueous solution, stir thoroughly, and dry to obtain powder B;

[0015] S3: calcining the powder B at 450° C. to 650° C. for 1 to 5 hours under an argon protective atmosphere to form a powder C;

[0016] S4: the powder C and the lithium source are mixed uniformly in a mass ratio of 4:1 to 19:1, added to the oil-based solution, placed in a heating container, and heated with stirring at 180° C. to 250° C. for 1 to 5 h under argon inert atmosphere at 3 to 8 MPa, taken out and dried to obtain powder D;

[0017] S5: The powder D is mixed evenly with an organic carbon source, added into a silane coupling agent solution with a mass fraction of 0.5% to 1%, and stirred evenly. After drying, the mixture is calcined at 700° C. to 800° C. for 1 h to 5 h under argon atmosphere protection to obtain a pre-lithiated silicon dioxide negative electrode material.

[0018] Preferably, in S1, the gas phase coating process includes CVD gas phase coating, specifically placing silicon 2 oxide in a CVD furnace, replacing the air in the furnace with argon gas, continuously introducing argon gas at 0.3L / min to 3L / min, then heating to 650℃ to 750℃ at 1℃ / min to 3℃ / min, introducing acetylene, and calcining for 1h to 2h, wherein the flow rate ratio of acetylene to argon is 2:1 to 1:2.

[0019] Preferably, in S2, the inorganic aqueous solution includes at least one of copper sulfate, silver nitrate, aluminum hydroxide, and aluminum dihydrogen phosphate aqueous solution, and the concentration of the inorganic aqueous solution is 0.1M to 1M;

[0020] In S2, the drying is performed by air drying at 50°C to 90°C.

[0021] Preferably, in S4, the lithium source includes one or more of lithium sheets, lithium ingots, and passivated lithium powder, and the oil-based solution includes one of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and dodecamethylcyclohexasiloxane.

[0022] Preferably, in S5, the organic carbon source includes one of sodium alginate, carboxymethyl cellulose and polyacrylic acid, and the mass ratio of powder D to the organic carbon source is 9:1 to 19:1.

[0023] Preferably, the silane coupling agent in S5 includes one of vinyltriethoxysilane, vinyltrimethoxysilane and γ-aminopropyltriethoxysilane.

[0024] (III) Beneficial effects

[0025] The present invention provides a pre-lithiation silicon oxide negative electrode material and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects:

[0026] The preparation method of the pre-lithiation silicon oxide negative electrode material of the present invention completes pre-lithiation under 3-8MPa conditions, so that the pre-lithiation reaction can occur at a temperature of 180°C to 250°C, which is much lower than the disproportionation temperature of silicon oxide, thereby reducing the disproportionation of silicon oxide during the pre-lithiation process; in addition, metallic lithium or passivated lithium powder with a lower melting point is used as a lithium source, and an oil-based solvent is used as a dispersant to make the pre-lithiation reaction a uniform liquid phase reaction, thereby maintaining the uniform internal structure of silicon oxide. Therefore, the pre-lithiation silicon oxide negative electrode material prepared in this application is an amorphous silicon oxide containing a lithium silicate phase, and the internal structure is uniform. The preparation method of the pre-lithiation silicon oxide negative electrode material of the present invention first uses a hydrophobic carbon layer and a hydrophobic inorganic salt to passivate the surface of silicon oxide, and then performs a pre-lithiation reaction, which can reduce the damage to the surface structure of silicon oxide during the pre-lithiation process. Therefore, the pre-lithiation silicon oxide negative electrode material prepared in this application is an amorphous silicon oxide containing a lithium silicate phase, and the surface structure is uniform. It has a uniform internal structure and surface structure, so the pre-lithiation silicon oxide negative electrode material has excellent electrochemical properties.

[0027] The pre-lithiated silicon oxide negative electrode material of the present invention comprises an amorphous silicon oxide core containing a lithium silicate phase, the outer surface of the core is uniformly covered with a hydrophobic conductive carbon layer and a hydrophilic carbon layer in sequence, and a hydrophobic inorganic substance is uniformly dispersed between the hydrophobic conductive carbon layer and the hydrophilic carbon layer; the hydrophilic carbon layer improves the water system wettability and dispersibility of the pre-lithiated silicon oxide negative electrode material, so when preparing the aqueous electrode slurry, the pre-lithiated silicon oxide negative electrode material is more uniformly mixed with the conductive agent and the binder, so that the prepared electrode plate has good uniformity of performance; the hydrophobic inorganic substance improves the pre-lithiated silicon oxide The hydrophobicity of silicon negative electrode material reduces the dissolution of lithium silicate in the process of preparing aqueous electrode slurry. The dissolution of lithium silicate will cause the pH value of the aqueous electrode slurry to change, thereby reducing the adhesion between the aqueous electrode slurry and the current collector. At the same time, the dissolution of lithium silicate will also cause bubbles to form in the aqueous electrode slurry, thereby affecting the uniformity of coating the aqueous electrode slurry on the current collector. Therefore, the aqueous electrode slurry prepared by the pre-lithiated silicon oxide negative electrode material of the present invention has excellent coating uniformity and adhesion to the electrode sheet, and the prepared electrode has good performance stability.

[0028] The pre-lithiated silicon oxide negative electrode material prepared in this application and metal lithium form a half-cell for electrochemical performance testing, with a test rate of 0.1C (first time) + 0.5C (cycle), and a charge and discharge voltage of 0.005 to 1.5 V. The discharge specific capacity of the negative electrode sheet can reach 1630 to 1730 mAh / g, with an initial efficiency of 89.0% to 92.0%, and after 50 cycles, it can still maintain 89.9% to 90.9% of the capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 This is the SEM image of the amorphous pre-lithiated silicon oxide negative electrode material of Example 2.

[0031] Figure 2 This is the XRD diagram of the amorphous pre-lithiated silicon dioxide negative electrode material of Example 2. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0034] Example 1

[0035] Silicon oxide with a particle size of 5 μm is placed in a CVD furnace, and argon is used to replace the air in the furnace. Argon is continuously introduced at 0.3 L / min, and then the temperature is raised to 450°C at 1°C / min. Acetylene is introduced with an acetylene gas flow rate of 0.6 L / min. After calcination for 1 hour, the surface of the silicon oxide powder is coated with a 6 nm hydrophobic conductive carbon layer.

[0036] Then pour into 0.1M copper sulfate aqueous solution and stir thoroughly, dry with blast at 50℃, place under argon protection and calcine at 650℃ for 1h, and the material surface material is dehydrated to form copper oxide hydrophobic inorganic matter. Then mix with lithium sheet at a mass ratio of 4:1 and add to octamethylcyclotetrasiloxane, place in a stirring hydrothermal kettle, stir and heat at 180℃ for 1h in an argon inert atmosphere at 3MPa, take out and dry, and then mix with sodium alginate at a mass ratio of 9:1, add to a 0.5% vinyl triethoxysilane solution and stir evenly, dry and calcine at 700℃ under argon atmosphere for 1h, and coat the surface of the material with a hydrophilic carbon layer with a thickness of 34nm to obtain an amorphous pre-lithiated silicon oxide negative electrode material.

[0037] The obtained amorphous pre-lithiated silicon oxide negative electrode material and metallic lithium were used to form a half-cell for electrochemical performance testing, with a test rate of 0.1C (first time) + 0.5C (cycle) and a charge and discharge voltage of 0.005-1.5V. The discharge specific capacity of the negative electrode sheet can reach 1630mAh / g, with an initial efficiency of 92.0%, and after 50 cycles, it can still maintain 90.2% of the capacity.

[0038] Example 2

[0039] Silicon oxide with a particle size of 6 μm is placed in a CVD furnace, and argon is used to replace the air in the furnace. Argon is continuously introduced at 1 L / min, and then the temperature is raised to 700°C at 1.5°C / min. Acetylene is introduced with an acetylene gas flow rate of 1 L / min. The furnace is calcined for 1.5 hours. The surface of the silicon oxide powder is coated with a 10 nm hydrophobic conductive carbon layer. The powder is then poured into a 0.3 M aluminum hydroxide aqueous solution and stirred thoroughly. The powder is dried at 60°C with forced air, and then calcined at 460°C under argon protection for 1 hour. The material surface is dehydrated to form aluminum oxide hydrophobic inorganic matter. Then, the mixture was mixed with lithium ingot at a mass ratio of 8:1, added into decamethylcyclopentasiloxane solution, placed in a stirring hydrothermal autoclave, heated at 200°C for 2 h under 4 MPa in an argon inert atmosphere, taken out and dried, and then mixed with carboxymethyl cellulose at a mass ratio of 10:1, added into a 0.6% vinyltrimethoxysilane solution and stirred evenly. After drying, the mixture was calcined at 730°C for 2 h under argon atmosphere protection, and a hydrophilic carbon layer with a thickness of 30 nm was coated on the surface of the material to obtain an amorphous pre-lithiated silicon oxide negative electrode material, and its SEM and XRD patterns are shown in FIG. Figure 1 , 2 ,Depend on Figure 1 It can be seen that the surface of the amorphous pre-lithiated silicon oxide negative electrode material is uniformly coated with a hydrophilic carbon layer. Figure 2 It can be seen that the amorphous pre-lithiated silicon oxide negative electrode material is an amorphous silicon oxide containing a lithium silicate phase (Li2SiO3) and does not contain silicon characteristic peaks. Therefore, its internal structure is relatively uniform.

[0040] The obtained amorphous pre-lithiated silicon oxide negative electrode material and metallic lithium were used to form a half-cell for electrochemical performance testing, with a test rate of 0.1C (first time) + 0.5C (cycle) and a charge and discharge voltage of 0.005-1.5V. The discharge specific capacity of the negative electrode sheet can reach 1730mAh / g, with an initial efficiency of 91.3%. After 50 cycles, it can still maintain 89.9% of the capacity.

[0041] Example 3

[0042] Silicon oxide with a particle size of 7 μm is placed in a CVD furnace, and argon is used to replace the air in the furnace. Argon is continuously introduced at 1 L / min, and then the temperature is raised to 760°C at 2°C / min. Acetylene is introduced with an acetylene gas flow rate of 2 L / min. The silicon oxide powder is calcined for 3 hours. The surface of the silicon oxide powder is coated with a 15 nm hydrophobic conductive carbon layer. The powder is then poured into a 0.8 M silver nitrate aqueous solution and stirred thoroughly. The powder is dried at 80°C with forced air, and then calcined at 500°C under argon protection for 3 hours. The material surface is dehydrated to form silver oxide hydrophobic inorganic matter. Then, the mixture was mixed evenly with passivation lithium powder at a mass ratio of 15:1, added into a dodecamethylcyclohexasiloxane solution, placed in a stirring hydrothermal autoclave, and heated at 220°C for 3 hours at 5MPa in an argon inert atmosphere. The mixture was taken out and dried, and then mixed evenly with polyacrylic acid at a mass ratio of 10:1. The mixture was added into a 0.8% mass fraction of γ-aminopropyltriethoxysilane solution and stirred evenly. After drying, the mixture was calcined at 750°C for 3 hours under the protection of an argon atmosphere, and a hydrophilic carbon layer with a thickness of 18 nm was coated on the surface of the material to obtain an amorphous pre-lithiated silicon oxide negative electrode material.

[0043] The obtained amorphous pre-lithiated silicon oxide negative electrode material and metallic lithium were used to form a half-cell for electrochemical performance testing, with a test rate of 0.1C (first time) + 0.5C (cycle) and a charge and discharge voltage of 0.005-1.5V. The discharge specific capacity of the negative electrode sheet can reach 1630mAh / g, with an initial efficiency of 89.3%. After 50 cycles, it can still maintain 90.9% of the capacity.

[0044] Example 4

[0045] Silicon oxide with a particle size of 8 μm is placed in a CVD furnace, and argon is used to replace the air in the furnace. Argon is continuously introduced at 1 L / min, and then the temperature is raised to 800°C at 3°C / min. Acetylene is introduced with an acetylene gas flow rate of 2 L / min. The silicon oxide powder is calcined for 5 hours. The surface of the silicon oxide powder is coated with an 18 nm hydrophobic conductive carbon layer. The powder is then poured into an aqueous solution of 1M aluminum dihydrogen phosphate solution and stirred thoroughly. The powder is dried with air at 90°C and calcined at 650°C under argon protection for 5 hours. The surface material of the material is dehydrated to form aluminum phosphate and aluminum metaphosphate hydrophobic inorganic substances. Then, the mixture was mixed evenly with passivation lithium powder at a mass ratio of 19:1, added into a dodecamethylcyclohexasiloxane solution, placed in a stirring hydrothermal autoclave, and heated at 250°C for 5 hours at 8MPa in an argon inert atmosphere. The mixture was taken out and dried, and then mixed evenly with polyacrylic acid at a mass ratio of 10:1. The mixture was added into a 1% mass fraction of γ-aminopropyltriethoxysilane solution and stirred evenly. After drying, the mixture was calcined at 800°C for 5 hours under the protection of an argon atmosphere, and a hydrophilic carbon layer with a thickness of 8nm was coated on the surface of the material to obtain an amorphous pre-lithiated silicon oxide negative electrode material.

[0046] The obtained amorphous pre-lithiated silicon oxide negative electrode material and metallic lithium were used to form a half-cell for electrochemical performance testing, with a test rate of 0.1C (first time) + 0.5C (cycle) and a charge and discharge voltage of 0.005-1.5V. The discharge specific capacity of the negative electrode sheet can reach 1690mAh / g, with an initial efficiency of 89.0%, and after 50 cycles, it can still maintain 90.1% of the capacity.

[0047] Comparative Example 1

[0048] Silicon oxide with an average particle size of 4 μm is placed in a vapor deposition furnace, and argon and acetylene are introduced at 850°C for carbon coating for 2 hours to obtain a silicon oxide-based negative electrode material, wherein the gas flow rate of argon is 150 ml / min, and the gas flow rate of acetylene is 100 ml / min, and then mixed evenly with passivation lithium at a mass ratio of 10:1, and calcined at 800°C in an argon atmosphere for 3 hours to obtain pre-lithium silicon oxide.

[0049] The negative electrode material prepared above was used to prepare a pole piece as a reference positive electrode, and metal lithium was used as a reference negative electrode. A half-cell was formed with a separator and an electrolyte to perform an electrochemical performance test. The test rate was 0.1C (first time) + 0.5C (cycle), and the charge and discharge voltage was 0.005-0.8V. The discharge specific capacity of the negative electrode piece can reach 1100mAh / g, with an initial efficiency of 86.3%. After 20 cycles, the capacity retention rate was only 56.2%.

[0050] The electrical properties of the negative electrode materials prepared in Examples 1-4 are significantly better than those in Comparative Example 1. This is because the preparation method of the pre-lithiated silicon oxide negative electrode material of the present invention completes pre-lithiation under a high-pressure environment, so that the pre-lithiation reaction can occur at a temperature of 180°C to 250°C, which is much lower than the disproportionation temperature of silicon oxide, thereby reducing the disproportionation of silicon oxide during the pre-lithiation process; in addition, metallic lithium or passivated lithium powder with a lower melting point is used as a lithium source, and an oil-based solvent is used as a dispersant to make the pre-lithiation reaction a uniform liquid phase reaction, thereby maintaining the uniform internal structure of silicon oxide. Therefore, the pre-lithiated silicon oxide negative electrode material prepared in the present application is an amorphous silicon oxide containing a lithium silicate phase, and the internal structure is uniform.

[0051] The preparation method of the pre-lithiated silicon oxide negative electrode material of the present invention first uses a hydrophobic carbon layer and a hydrophobic inorganic salt to passivate the surface of silicon oxide, and then performs a pre-lithiation reaction, which can reduce the damage to the surface structure of silicon oxide during the pre-lithiation process. Therefore, the pre-lithiated silicon oxide negative electrode material prepared in this application is an amorphous silicon oxide containing a lithium silicate phase, and the surface structure is uniform. Therefore, the pre-lithiated silicon oxide negative electrode material prepared by the preparation method of the present invention has excellent electrochemical properties.

[0052] The pre-lithiated silicon oxide negative electrode material of the present invention comprises an amorphous silicon oxide core containing a lithium silicate phase, the outer surface of the core is uniformly covered with a hydrophobic conductive carbon layer and a hydrophilic carbon layer in sequence, and a hydrophobic inorganic substance is uniformly dispersed between the hydrophobic conductive carbon layer and the hydrophilic carbon layer; the hydrophilic carbon layer improves the water system wettability and dispersibility of the pre-lithiated silicon oxide negative electrode material, so when preparing the aqueous electrode slurry, the pre-lithiated silicon oxide negative electrode material is more uniformly mixed with the conductive agent and the binder, so that the prepared electrode plate has good uniformity of performance; the hydrophobic inorganic substance improves the pre-lithiated silicon oxide The hydrophobicity of silicon negative electrode material reduces the dissolution of lithium silicate in the process of preparing aqueous electrode slurry. The dissolution of lithium silicate will cause the pH value of the aqueous electrode slurry to change, thereby reducing the adhesion between the aqueous electrode slurry and the current collector. At the same time, the dissolution of lithium silicate will also cause bubbles to form in the aqueous electrode slurry, thereby affecting the uniformity of coating the aqueous electrode slurry on the current collector. Therefore, the aqueous electrode slurry prepared by the pre-lithiated silicon oxide negative electrode material of the present invention has excellent coating uniformity and adhesion to the electrode sheet, and the prepared electrode has good performance stability.

[0053] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0054] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A pre-lithiated silicon oxide negative electrode material, characterized in that: The core of the pre-lithiated silicon oxide negative electrode material comprises amorphous silicon oxide containing a lithium silicate phase, the outer surface of the core is uniformly covered with a hydrophobic conductive carbon layer and a hydrophilic carbon layer in sequence, and a hydrophobic inorganic substance is uniformly dispersed between the hydrophobic conductive carbon layer and the hydrophilic carbon layer; The method for preparing the pre-lithiated silicon dioxide negative electrode material comprises the following steps: S1: Silicon oxide particles are coated with a hydrophobic conductive carbon layer on the surface of silicon oxide to obtain powder A; S2: Pour the powder A into an inorganic aqueous solution, stir thoroughly, and dry to obtain powder B; S3: calcining the powder B at 450° C. to 650° C. for 1 to 5 h under an argon protective atmosphere to form a powder C; S4: the powder C and the lithium source are mixed uniformly in a mass ratio of 4:1 to 19:1, added to the oil-based solution, placed in a heating container, and heated with stirring at 180°C to 250°C for 1 to 5 h under 3 to 8 MPa in an argon inert atmosphere, and then taken out and dried to obtain powder D; S5: the powder D is mixed evenly with an organic carbon source, added into a silane coupling agent solution with a mass fraction of 0.5% to 1%, stirred evenly, dried, and calcined at 700° C. to 800° C. for 1 h to 5 h under argon atmosphere protection to obtain a pre-lithiated silicon dioxide negative electrode material; The lithium source includes one or more of lithium sheets, lithium ingots, and passivated lithium powder.

2. The pre-lithiated silicon dioxide negative electrode material according to claim 1, characterized in that: The amorphous silicon oxide particle size of the lithium silicate phase is 5-8 μm, the thickness of the hydrophobic conductive carbon layer is 25-40 nm, and the thickness of the hydrophilic carbon layer is 10-30 nm.

3. The pre-lithiated silicon dioxide negative electrode material according to claim 1, characterized in that: The hydrophobic inorganic substance includes one or more of copper oxide, aluminum oxide, silver oxide, aluminum phosphate, and aluminum metaphosphate.

4. The pre-lithiated silicon dioxide negative electrode material according to claim 1, characterized in that: In S1, the gas phase coating process includes CVD gas phase coating, specifically placing silicon 2 oxide in a CVD furnace, replacing the air in the furnace with argon gas, continuously introducing argon gas at 0.3 L / min to 3 L / min, then heating to 650°C to 750°C at 1°C / min to 3°C / min, introducing acetylene, and calcining for 1 h to 2 h, wherein the flow rate ratio of acetylene to argon is 2:1 to 1:

2.

5. The pre-lithiated silicon dioxide negative electrode material according to claim 1, characterized in that: In S2, the inorganic aqueous solution includes at least one of copper sulfate, silver nitrate, aluminum hydroxide, and aluminum dihydrogen phosphate aqueous solution, and the concentration of the inorganic aqueous solution is 0.1 M to 1 M; In S2, the drying is performed by air drying at 50°C to 90°C.

6. The pre-lithiated silicon dioxide negative electrode material according to claim 1, characterized in that: In S4, the oil-based solution includes one of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and dodecamethylcyclohexasiloxane.

7. The pre-lithiated silicon dioxide negative electrode material according to claim 1, characterized in that: In S5, the organic carbon source includes one of sodium alginate, carboxymethyl cellulose and polyacrylic acid, and the mass ratio of powder D to the organic carbon source is 9:1 to 19:

1.

8. The pre-lithiated silicon dioxide negative electrode material according to claim 1, characterized in that: The S5, silane coupling agent includes one of vinyl triethoxy silane, vinyl trimethoxy silane, and γ-aminopropyl triethoxy silane.

Citation Information

Patent Citations

  • Low-residual-alkali long-circulation silicon monoxide carbon material and preparation method thereof

    CN116487551A

  • High-stability silicon-based negative electrode material and preparation method and application thereof

    CN116504955A